Degree of financialization and energy efficiency in Sub-Saharan Africa: Do institutions matter? - Philip Kofi Adom; Franklin Amuakwa-Mensah; Salome Amuakwa-Mensah (Financial Innovation, 2020)
The United Nations Sustainable Development Goal 7 emphasizes the need for economies around the world to double their efforts in energy efficiency improvements. This is because improvements in energy efficiency can trigger economic growth and considered as one of the 'green' growth strategies due to its carbon free content. To this end, some empirical studies have investigated the nexus between economic growth and energy efficiency, but the effects of the latter on financial indicators have not been sufficiently studied in the literature, at least in developing economies like Africa. This study examines the effect of energy efficiency improvements on commercial bank profitability under different political regimes (i.e., autocratic and democratic political regimes); something previous literature had neglected. The study uses panel data, consisting of 43 African countries and the simultaneous System Generalized Method of Moments. We found that energy efficiency improvement is more likely to induce higher bank profitability in political institutions with the characteristics of centralization of power compared with those with decentralization of power. Furthermore, for the banking sector, the findings suggest that energy utilization behavior of clients should be included in the loan or credit valuation process. For the government, the agenda of energy efficiency should be aggressively pursued while taking cognizance of creating a political environment that weans itself from a "grandfathering" behavior.
Keywords: G15; G21; Q43; 650; Bank performance; Energy efficiency; Institution; Sub-Saharan Africa